Assessment of apparent metabolizable energy, and ileal amino acid digestibility of full-fat black soldier fly larvae (Hermetia illucens) in broiler chickens - Mohammad S. Alafif; Louwrens C. Hoffman; Daniel Cozzolino; M. Reza Abdollahi; Eugeni Roura; Ai Duc Nguyen; Elham A. Soumeh (Poultry Science, 2025)
Accurate determination of metabolizable energy and ileal amino acid (AA) digestibility is essential for optimizing poultry diets, as they provide critical insights into the energy and AA availability of feed ingredients. This experiment was split into two phases to determine apparent metabolizable energy (AME), nitrogen-corrected AME (AMEn), apparent (AID), and standardized ileal digestibility (SID) of AA for black soldier fly larvae (BSFL) produced on three different waste streams (A, H, L) as a protein-rich ingredient for broiler chickens. The AME and AMEn were determined using the substitution method in 14-day-old male broiler chickens, where two diets were formulated: a basal diet and a treatment diet. The basal diet was substituted by the test ingredient (BSFL) at 300 g/kg and fed to chickens for 7 days. The AME for BSFL-A, BSFL-H and BSFL-L were determined to be 23.14, 24.54 and 22.53 MJ/kg DM; and AMEn values were 22.95, 24.34 and 22.35, MJ/kg DM, respectively. The AME and AMEn values for BSFL streams were significantly higher (P < 0.05) than those of SBM, which had values of 14.67 MJ/kg DM and 14.54 MJ/kg DM, respectively. The AA SID coefficents of BSFL products were determined in 21-d-old broilers using semi-purified diets (the direct method) fed to chickens for 3 days with the digesta being obtained on d 24. A nitrogen-free diet was used to estimate endogenous AA losses. The overall mean of the AID of AAs in BSFLs ranged from 86.75 % to 89.17 %, while the SID ranged from 86.77 % to 89.17 %. No significant differences were observed for the AA digestibility of BSFL products from different waste streams. The SID of lysine, methionine, threonine, and valine of BSFL samples ranged from 89.14 to 90.15 %, 88.66–90.02 %, 81.48–84.76 % and 87.38–90.01 %, respectively. Overall, the results showed that full-fat BSFL grown on food waste streams, are a valuable source of energy and digestible AAs for broiler chickens. Their high nutritive value and sustainability suggest strong potential to partially or fully replace conventional protein sources, such as soybean meal, in broiler feed formulations.